Computed tomography findings of primary epiploic appendagitis as an easily misdiagnosed entity: Case series and review of literature - DEMİRBAŞ, BAHA TOLGA; ÖZDEMİR, BURCU; TÜRELİ, DERYA; TÜNEY, DAVUT; ERGELEN, RABİA (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2017)
BACKGROUND: Primer epiploic appendagitis (PEA) is an uncommon condition. METHODS: We retrospectively reviewed the clinical records and computed tomography (CT) findings of 45 patients with PEA. RESULTS: On the basis of physical examination and pain localization, presumptive clinical diagnosis was acute appendicitis (n=13), acute cholecystitis (n=2), acute diverticulitis (n=19), renal colic (n=7) and ovarian pathology (n=4). CONCLUSION: Although it has no characteristic clinical and laboratory features, CT is the best modality for accurate diagnosis of PEA.
Keywords: Appendagitis; epiploic; tomography; CT; DIVERTICULITIS; DIAGNOSIS; FEATURES